Nauka ne-já v rané orientalistice : buddhistický ateismus, evropský textualismus a protestantská východiska - Skopal, Vilém (2024)
The beginnings of the academic study of Buddhism date back to late 18th century reaching its culmination by the middle of the 19th century with the works of E. Burnouf. Since this period was crucial for the formation of the field, it is necessary to understand how the Orientalists of the time understood the main Buddhist teaching of not-self (anatman). In line with contemporary postcolonial studies, the paper argues for a pivotal role of textualism in the early Orientalist perspective. It further shows the Protestant bias in orienting research toward textual evidence while ignoring all other data, such as material culture. Guided by such a presupposition, early Orientalists assumed that the teaching of not-self was fully explained in Buddhist scriptures, neglecting to explore its implications for living practices. Furthermore, the examination of Buddhist texts by early Orientalists was constrained by the intra-religious debates that prevailed in nineteenth century Europe, where questions about the possibility of atheism and natural religion dominated. Consequently, any attempt to explain the concept of not-self was circumscribed by questions such as the belief in God among Buddhists, the immortality of the soul in Buddhism, and the nature of nirvana as either the annihilation of the soul or its absorption into Divinity. For these reasons, I do not see Buddhists of the 19th century in early Orientalist discourse, but rather Orientalists themselves, prejudiced by their own religious biases.